Studi Penataan Pedagang Kaki Lima (PKL) di Pantai Manakarra Kota Mamuju Kabupaten Mamuju - Rendi Pratama; Syafri Syafri; Rusneni Ruslan (Journal of Urban Planning Studies, 2021)
The purpose of this research is to find out how the direction of the arrangement of street vendors on Manakarra Beach, Mamuju City. Regency. Mamuju. The variables used consisted of 4, namely: (1) Policy; (2) Education Level; (3) Economic level; (4) Supervision. The analytical method used is in the form of qualitative descriptive analysis and multiple linear analysis. Manakarra Beach is an Artificial Nature Tourism Object in the form of a beach located on Jl. Yos Sudarso, Kel. Rimuku, Kec. Mamuju, Kab. Mamuju, which is the center of Mamuju City. Departing from the description above where the focus of this research is the street vendors (PKL) who are on Manakarra Beach itself. Where the street vendors (PKL) sell on the shoulder of the road and sidewalk, so that there is a need for an effort to organize and supervise so that the street vendor activities do not interfere with the activities and mobility of the population or the community on Jalan Yos Sudarso. In addition, there is also a lack of awareness of tourists on Manakarra Beach towards the surrounding environment, this is evidenced by the presence of food packages and plastic bottles scattered at several points on Mankarra Beach. This of course was also praised by the existence of street vendors on Manakarra Beach itself. So that better structuring and supervision measures are needed.